The ''Crisis'' of Humanities and Literary Criticism - KALANTARYAN, ZHENYA (Bulletin of Yerevan University B: Philology, 2021)
Concerns about the crisis in human sciences have today become commonplace in various periodicals and in public discourse. This article attempts to disclose the reasons for such thinking. The study of certain facts allows the author to conclude that therapid development of new technologies and technical sciences, the universally increasingly pragmatic thinking, as well as ideological changes in post-Soviet countries have incurred new requirements, in the meeting of which literary studies has reduced competitiveness. Literary criticism, the component of literary studies more closely related to reality, reflects the above-mentioned changes more vividly and thus becomes a more frequent target of discontent.
Keywords: human sciences, literary studies, literary criticism, new technologies, crisis, journalism, methodology, value system, poetics and competitiveness